The Effect of Digital Literacy Towards EFL Students’ Reading Comprehension - Afifah Mufidati (Indonesian Journal of Foreign Language Studies, 2024)
This research is about junior high school students' digital literacy skills. Digital literacy is exposed to all sources connected to the Internet, and digital media is used to show readers about literacy options, either active or passive form reading activity. This research aims to explore junior high school students in their first grade who are 12-13 years old. Junior high school students tend to be exposed to more variance of digital literacies to enjoy a fun environment in learning English. The number of participants here was 67 students. This study registered quantitative research design. The Independent sample t-test and effect size by Cohens were used to measure the effect of low and high students' digital literacy levels. The finding showed that the score was significant, d=3.80>0.8, which showed that digital literacy skills significantly affect students' reading comprehension. Further research should emphasize other skills and specified digital literacy sources in EFL classrooms.